2005
DOI: 10.5144/0256-4947.2005.46
|View full text |Cite
|
Sign up to set email alerts
|

Documentation and coding of medical records in a tertiary care center: a pilot study

Abstract: BACKGROUNDSince the medical record is the major source of health information, it is necessary to maintain accurate, comprehensive and properly coded patient data. We reviewed 300 medical records from patients at King Faisal Specialist Hospital and Research Center, representing four departments (medicine, surgery, pediatrics and obstetrics and gynecology).METHODSThe records were audited following the guidelines of the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
1
18
1
1
Order By: Relevance
“…In a study, a 21% increase in coding accuracy was found due to high-quality documentation (Farhan et al, 2005). Further, it has been shown that a computerized database significantly improved the accuracy and completeness of documentation and diagnostic coding (van Walraven & Demers, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…In a study, a 21% increase in coding accuracy was found due to high-quality documentation (Farhan et al, 2005). Further, it has been shown that a computerized database significantly improved the accuracy and completeness of documentation and diagnostic coding (van Walraven & Demers, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…The quality of the case studies, research, statistics, scientific information, depending on the quality of content that is serving the documentary record. These qualities, often in terms of being a true complete availability, timely and legibility described ( 6 ). The new medicine, producing large amounts of data looking, but always there is a deep gap between data collection to understand and interpret the data available from the other side, they are bulky and confusing ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In primary health care (PHC), e-records have uses beyond simply retrieval of patient information; for example, warnings of allergies and drug interactions, developing management protocols for chronic illness, generating pre-appointment reminders and establishing communication links between different levels of care [2,3]. E-records are assumed to improve the quality of documentation over paper-based medical records via automatic reminders to health-care professionals of important data that are missing [4,5]. Some authors, however, have warned that inadequate computer skills or lack of training of health professionals together with limitations in erecords software could result in the data in e-records being truncated compared with paper-based records [6].…”
Section: Introductionmentioning
confidence: 99%